POLITICS DISCRETIONARY FUND BUDGET OF REGIONAL INCOME AND EXPENDITURE BEFORE AND ELECTION IN 2015 IN SAMARINDA CITY - Muhammad Habibi; Suswanta Suswanta (Universitas Muhammadiyah Yogyakarta, 2019)
Expenditures on grants (Hibah) and sosial assistance (Bansos) which are included in the category of discretionary funds are very vulnerable to be used as campaign funds to gain popularity of incumbent couples. The purpose of this study is to investigate the possibility of an indication of abuse of discretionary funds in the APBD. This study used an interactive analysis model using three stages, namely; data condensation, presentation of concluding data, and verification. The results of this study indicated that the allocation of regional expenditures on grants and sosial assistance that carried out regional head election (Pemilukada) with the incumbent candidates is greater than before the election, which means there was the use of incumbent discretionary funds for their political interests. The allocation of regional discretionary funds that carried out the election with incumbent candidates was greater than the regions that do not implement the election. Increased of discretionary funds continue to occur despite the unhealthy / deficit regional financial condition. It coupled with the findings of the allocation of expenditure of goods distributed through 100 SKPD of Rp. 504,938,020,140,34 to the public. This was a strong indication that the incumbent was trying to keep providing the assistance to attract voters on the Pemilukada in 2015.